PENGARUH FASILITAS PERPAJAKAN, UKURAN PERUSAHAAN, RETURN ON ASSETS (ROA) DAN KOMITE AUDIT TERHADAP MANAJEMEN PAJAK - Sutomo, Aisha Rizhantika; Finanto, Hasto; Ismawanto , Totok (E-Jurnal Akuntansi TSM, 2025)
Tax is a mandatory contribution imposed on individuals and corporations without direct compensation, intended for the welfare of society. However, many companies employ tax management strategies to minimize their tax burden, raising concerns about compliance and corporate governance. This study investigates the effect of tax facilities, firm size, profitability (Return on Assets/ROA), and audit committees on tax management among healthcare companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Agency theory serves as the theoretical foundation to explain the interaction between independent and dependent variables. The research adopts a quantitative approach with purposive sampling, yielding 45 observations from 15 companies, and data analysis was conducted using SPSS. The results indicate that tax facilities, firm size, ROA, and audit committees simultaneously have a significant effect on tax management. Partially, only tax facilities show a significant negative influence, implying that the availability of legal tax incentives reduces the need for aggressive tax practices. This finding supports earlier studies which highlight that tax facilities encourage firms to comply with regulations rather than exploit loopholes. The study provides insight for policymakers and companies to design efficient yet compliant tax strategies, strengthening trust between regulators, stakeholders, and corporations.